Why not be "smarter"? Examining the factors that influence the behavioral intentions of non-smartphone users. Issue 1 (6th February 2017) - Lin, Chen-Yu; Chao, Yu-Chuang; Tang, Tzy-Wen
Abstract : Purpose: Despite the evident and dramatic increase in smartphone usage worldwide, some consumers continue to use traditional mobile phones. The purpose of this paper is to investigate the behavioral intentions of these laggard and non-smartphone users. Design/methodology/approach: This current study examines the effects of consumer demographics, psychographics, and smartphone characteristics on the intentions of non-smartphone consumers to switch or resist the use of smartphones. Data were collected using a convenience sample of non-smartphone users in Taiwan. The proposed model is tested using the consistent partial least squares (PLSc) path modeling technique. Findings: PLSc results indicate that consumer psychographics and smartphone characteristics play more important roles than consumer demographics. Specifically, price consciousness, nostalgia, and perceived ease of use are good predictors of intention to switch, whereas perceived usefulness and ease of use are strong predictors of the intention to resist smartphone adoption. Practical implications: The results of this study have implications for mobile phone vendors and mobile manufacturers who target non-smartphone users or laggard adopters. Originality/value: This study is among the few that focus on non-smartphone users' perceptions of smartphones. Hence, this empirical study could contribute to the development and testing of theories related to the smartphone adoption process.